Sustainable and resilient construction: Current status and future challenges. (20th September 2020) - Murtagh, Niamh; Scott, Lloyd; Fan, Jingli
Abstract: The construction industry globally is one of the most environmentally damaging of sectors. Additionally, the resources consumed and the operational energy requirements of buildings are 'locked-in', potentially for decades. The Intergovernmental Panel on Climate Change has recognised construction as a sector in which significant improvements can, and indeed must, be made. But the industry is often argued to be unique, in its multiplicity of stakeholders, transient organisational structures, avoidance of risk and impact on society. The current Virtual Special Issue (VSI) sought to bring together a collection of papers on progress and potential for improvement in the construction sector, in terms of both sustainability and resilience to the changing climate. A total of 34 papers form the VSI. Insights from social science include the need for more holistic perspectives at multiple levels, from buildings to urban plans, and the centrality of human relationships, through leadership, collaboration and along supply chains. Insights from a technology perspective include BIM applications for green and off-site construction, enhanced estimation of construction waste, and developments in materials. Insights on low-carbon construction include evidence that reducing both costs and emissions in the construction sector is viable. This editorial reviews the VSI papers and makes a number of recommendations including the need to recognize that values and understanding change over time and that leadership and human decision-making are essential factors for transformation. Alongside the progress described on sustainability in multiple areas, the editorial calls for an invigorated research focus on how construction can adapt the built environment to the changing future that is before us all. Highlights: Reducing both costs and emissions in construction is viable. Human relationships (leadership, supply chain, project) essential for transformation. Business decisions rarely utilitarian but set in social contexts. Evaluation methods must address temporal nature of value and sustainability. Insufficient research attention on climate resilience in the built environment.